Application of the modified Bai-Wierzbicki model for the prediction of ductile fracture in pipelines. (March 2019) - Keim, V.; Nonn, A.; Münstermann, S.
Abstract: The complex mechanical and corrosive loads of modern pipeline systems transporting oil, natural gas and C O 2 impose steadily increasing requirements on material properties. The majority of current design standards still limit the application of modern high toughness linepipe steels due to the simple specification of material requirements in terms of energy levels from Charpy impact or Battelle Drop-Weight-Tear (BDWT) tests. In consequence, research activities have been conducted recently aiming at developing modified or novel experimental methods for the characterization of the ductile fracture behavior. To quantify the effects of various parameters on fracture behavior and derive suitable correlations, it is necessary to accompany these activities by numerical simulations with appropriate ductile damage models. In this paper, the MBW model is applied to study the structural behavior of pipelines in ductile fracture regime. Due to its precise incorporation of the underlying load conditions, the damage model is successfully used to simulate the slant fracture behavior in Battelle Drop weight tear test specimens and pipe sections. In comparison to ductile damage models applied in former studies, namely the Gurson-Tvergaard-Needleman and Cohesive Zone model, the presented numerical methodology allows for a more detailed investigation of loading, material and geometry effects on fracture and crack arrest behavior of pipelines.